Assessment of attentional processes in patients with anxiety-depressive disorders using virtual reality. - Camacho-Conde, José Antonio; Legarra, Leire; Bolinches, Victoria; Cano, Patricia; Guasch, Mónica; Llanos Torres, María; Mejías, Miguel; Climent, Gema (MDPI, 2021)
To characterize the attention deficits in one-hundred-fifteen participants, comprising two types of clinical profiles (affective and anxiety disorder), through a test of continuous VR execution. Method: Three tests (i.e., Nesplora Aquarium, BDI, and STAI) were used to obtain a standardized measure of attention, as well as the existence and severity of depression and anxiety, respectively. Results: Significant differences (CI = 95%) were found between the control group and the group with depression, in variables related to the speed of visual processing (p = 0.008) in the absence of distractors (p = 0.041) and during the first dual execution task (p = 0.011). For scores related to sustained attention, patients with depression and those with anxiety did not differ from controls. Our results suggest attentional deficits in both clinical populations when performing a continuous performance test that involved the participation of the central executive system of working memory.
CC BY
Keywords: Depresión mental - Tratamiento - Innovaciones tecnológicas; Realidad virtual - Uso terapéutico; Atención; Depresión